Determination of the Phenolic Content in Iranian Trehala Manna and Evaluation of Their Antioxidant Effects. (1st September 2021) - Darikvand, Farzaneh; Ghavami, Mehrdad; Honarvar, Masoud
Abstract : One of the most challenging issues in the food and pharmaceutical industries is finding effective and safe antioxidants from natural resources compared to their synthetic compounds, which have side effects. In this regard, Trehala manna was considered a great antioxidant source categorized as the major type of manna produced naturally and by the Echinops plant in response to insect activity. In this study, the antioxidant activity and phenolic content of the numerous Trehala manna in Echinops sp. have been investigated. Different methods of radical scavenging activity comprising 2, 2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and 2, 2-diphenyl-1-picrylhydrazyl (DPPH) have been investigated to evaluate antioxidant activity. The phenolic contents were measured by Folin–Ciocalteu and standard phytochemical methods. Quantitative and qualitative amounts of phenolic content, including caffeic, ferulic, coumaric, syringic, and hydroxybenzoic acids, were quantified by high-performance liquid chromatography (HPLC). The results indicated the significant changes in the amounts of phenolics and the antioxidant properties in Trehala manna samples, based on the place of collection. Based on results, antioxidant capacity detected by DPPH and ABTS tests showed the IC50 values of 40–94  µ g/mL and 28–72  µ g/mL, respectively. Results of the FRAP test represented very strong ferric ion reducing activities (0.04–0.83 mmol Fe2+/g). Ferric ion reducing data were not markedly different from ABTS and DPPH ones. These samples also presented the highest phenolic content (1.32–2.28 mg GAE/100 g). Jahrom Trehala manna was the highest in both phenolic content and antioxidant value, while Sabzevar was the lowest. We found a significant relationship between the antioxidant values and total phenolic counts. It indicates that the phenolics contribute to the observed antioxidant activities of these samples.